Achieving ultrastability and efficient lithium storage capacity with high-energy iron(ii) oxalate anode materials by compositing Ge nano-conductive sites. Issue 6 (18th January 2023) - Song, Tingyu; Gao, Geng; Cui, Dingfang; Wang, Chong; Zhang, Hui; Liang, Feng; Yang, Bin; Zhang, Keyu; Yao, Yaochun
Abstract : Transition metal oxalates (TMOxs, represented by iron oxalate) have attracted considerable interest in anode materials due to their excellent lithium storage properties and consistent cyclic performance. Abstract : Transition metal oxalates (TMOxs, represented by iron oxalate) have attracted considerable interest in anode materials due to their excellent lithium storage properties and consistent cyclic performance. Although investigations into their electrochemical capabilities and lithium storage mechanisms are gradually deepening, the complex and varied electrochemical reactions in the initial cycle, poor inherent conductivity, and high irreversible capacity constrain their further development. Herein, to solve the above-mentioned problems, we controlled the hydrothermal synthesis conditions of iron oxalate with the assistance of organic solvents, which induced the growth of iron oxalate crystals with nano Ge metal as the core. The metal Ge space sites compounded to the stacked iron oxalate particles act as conductive nodes and metal frames, which enhances both the strength of iron oxalate samples and electronic conductivity and lithium-ion diffusion inside the electrode materials. This special structure enhances the electrochemical activity of iron oxalates and improves their lithium storage capability. The iron oxalate @ nano Ge metal composite (FCO@Ge-1) exhibits an excellent cycling performance and an appreciable reversible specific capacity (1090 mA h g −1 after 200 cycles at 1 A g −1 ). The obvious polarization and variation of the electrochemical reaction in the initial cycle of iron oxalate are reduced by compositing nano Ge metal. It is demonstrated that nano Ge metal can promote reversible capacity retention from 67.72% to 80.69% in the early cycles. The distinctive structure of iron oxalate @ nano Ge metal composite provides a fresh pathway to enhance oxalate electrochemical reversible lithium storage activity and develop high-energy electrode material by constructing composite space conductive sites.